Short and amusing: The relationship between title characteristics, downloads, and citations in psychology articles. (February 2014) - Subotic, Sinisa; Mukherjee, Bhaskar
The aim of this study was to conduct a unified investigation of various, previously mostly individually studied scientific article title characteristics, like: title length, type, amusement and pleasantness, and specific title 'markers' (e.g. colons, attention-grabbing words etc.) in relation to subsequent article citation and download rates. Based on a sample of 129 psychology ScienceDirect's Top 25 Hottest Articles (i.e. highly downloaded articles) and 129 articles not appearing on the Top 25 list (i.e. less downloaded articles), we determined that the most relevant title characteristics were the title length and the title amusement/humour. The partial least squares model revealed that shorter titles were associated with more citations, but the effect was fully mediated by the journal impact, suggesting that the observed citational benefits of the shorter titles might be an artefact of some higher journal impact related attribute (perhaps editorial or peer review process). Title amusement level was slightly correlated with downloads, but with no association with citations. Additionally, downloads correlated positively with citations, and more amusing titles tended to be shorter. While these findings are limited to the psychology discipline only, our results suggest that the integrative structural approach is promising and that more research following this paradigm is needed before empirically grounded recommendations for good title writing can be given.